Catalytic H2 evolution/oxidation in [FeFe]-hydrogenase biomimetics: account from DFT on the interplay of related issues and proposed solutions. (21st September 2020) - Arrigoni, Federica; Bertini, Luca; Breglia, Raffaella; Greco, Claudio; De Gioia, Luca; Zampella, Giuseppe
Abstract : A DFT overview on selected issues regarding diiron catalysts related to [FeFe]-hydrogenase biomimetic research, with implications for both energy conversion and storage strategies. Abstract : This perspective aims at illustrating a computational viewpoint on some specific issues concerning structure–activity relationships related to [FeFe]-hydrogenase ([FeFe]-H2 ase) biomimicry. Most of the research outlined herein has been addressed by means of density functional theory (DFT) based tools, in some cases in conjunction with experimental techniques. The number of computational, experimental and mixed approach studies on the "hydrogenase models" topic is extraordinarily high. Accordingly, several comprehensive reviews have been published over the last twenty years. Moreover, the number of iron compounds of increasing nuclearity that have been considered as "biomimetic models" of [FeFe]-H2 ase has grown exponentially over time. Additionally, the issues regarding some mismatches existing between the natural system and related synthetic analogues, are quite variegated. As a consequence of the countless examples that could be considered as related to "hydrogenase mimicry", the intent of the present contribution is to provide an account of a limited number of recent study cases, in which DFT has been employed to elucidate redox properties, reactivity issues of selected examples of diiron biomimicry. Herein the treated topics have been explicitly chosen to show how DFT has allowed us to rationalize and complement experimental observations, with a special focus on electrocatalysis aspects. Finally, the specific purpose of this perspective is to show how mutually intertwined are the various issues concerning a fascinating branch of biomimetic research.